PP.10.04: DETERMINANTS OF AORTIC STIFFNESS IN A LONG-LIVING POPULATION. (June 2015) - Pietri, P.; Vlachopoulos, C.; Ioakeimidis, N.; Alexopoulos, N.; Terentes-Printzios, D.; Abdelrasoul, M.; Gourgouli, I.; Chrysocoou, C.; Lazaros, G.; Stefanadis, C.; Tousoulis, D.
Abstract : Objective: Ikaria, the Greek island of the East Aegean, is among the five places in the world with the highest rates of octagenarians. Aortic stiffness, assessed by aortic pulse wave velocity (PWV), is an independent prognostic factor of cardiovascular and all-cause mortality. However, data on the assessment of aortic stiffness in long-living populations are lacking. The aim of the present study was to evaluate aortic stiffness in the inhabitants of Ikaria island, across a broad spectrum of age. Design and method: We studied a sample of the Ikaria island's inhabitants (N = 153). We divided the population into 4 age groups, each per decade: 1. 40–49 years old (N = 30), 2. 50–59 years old (N = 40), 3. 60–69 years old (N = 35) and 4. over 70 years of age (N = 48). Aortic stiffness was assessed by the measurement of carotid-femoral PWV using the Complior device. Laboratory evaluation was performed in all participants. Results: Systolic blood pressure (SBP) showed a gradual increase proportional to the advanced age group (from 131.1 ± 11.5 to 136.5 ± 15.1 to 143.6 ± 16.4 to 152.4 ± 21.7 mmHg, p < 0.01). On the contrary, no difference was observed in the levels of diastolic BP among groups (from 81.7 ± 6.4 to 83.5 ± 10.1 to 80.8 ± 7.3 to 81.6 ± 11.1 mmHg, p = NS). Pulse wave velocity increased gradually across the 4 groups of age (from 7.96 ± 0.95 to 8.76 ± 1.25 to 9.89 ± 1.19 to 12.05 ± 2.62 m/s, respectively, p < 0.001). In linear regression analysis, PWV was independently related to age group (b = 0.62, p < 0.001), heart rate (b = 0.24, p < 0.001), mean BP (b = 0.20, p < 0.01), creatinine (b = 0.15, p = 0.02) and, inversely, to BMI (b = -0.13, p = 0.03) Conclusions: Age is a powerful determinant of aortic stiffness in the population of Ikaria island. Moreover, haemodynamic parameters, such as arterial pressure and heart rate, as well as kidney function are independently associated with aortic stiffness. Interestingly, obesity is inversely related to PWV, a finding suggesting a possible 'obesity paradox' effect. Future studies in other long-living populations need to confirm the present findings and shed light into the relationship of arterial stiffness with longevity.